Design and validation of a scale to identify stereotypes against indigenous people - Echeverría Echeverría, Rebelín (2013)
The aim of this study was to design and validate a scale to identify prejudices against indigenous people as a socially stigmatised and culturally relevant group in Mexican samples, and establishing gender differences in undergraduate students. A sample of 563 undergraduate students was drawn from Merida, the capital city, and inner towns in the state of Yucatan, Mexico. From the sample, 272 were women and 292 were men with an average age of 23.06 years. To measure beliefs scale was developed consisted of 50 Likert reagents to assess stereotypical beliefs toward indigenous people. Factor analysis threw five main factors. Results show that the scale has adequate psychometric qualities, including reliability and validity.